Regional groundwater flow dynamics and residence times in Chaudière-Appalaches, Québec, Canada: Insights from numerical simulations. Issue 2 (3rd April 2018) - Janos, D.; Molson, J.; Lefebvre, R.
Abstract : As part of the Quebec PACES III provincial groundwater resources assessment programme (Programme d'acquisition des connaissances en eaux souterraines), a regional-scale two-dimensional numerical groundwater model was developed in the Chaudière-Appalaches region, Québec, Canada. The model considers groundwater flow, transport of groundwater age and the influence of a fault on the flow system and its implications for groundwater quality. By including deep and shallow flow systems, the study helps fill a knowledge gap with respect to intermediate flow systems and the role they would play during potential energy resource development including shale gas exploitation from the Utica Shale. Physical and chemical hydrogeological data, including an analysis of 14 C in dissolved inorganic carbon in sampled groundwater, supported a regional conceptual flow model forming the basis for numerical simulations. The numerical model is first calibrated to regional piezometry through a semi-automated workflow using the inverse model PEST. Although some evidence for deeper regional flow exists, the area appears to be dominated by local flow systems on maximum length scales of about 5 km, with significant flow through the top 40 to 60 m of the fractured sedimentary rock aquifer. This regional-scale flow model is also supported by the local hydrogeochemical signatures. Simulated mean groundwater ages show young shallow water of < 100 years with rapid increases in age with depth suggesting diffusion-controlled age evolution. Groundwater age is likely being perturbed in the vicinity of the Jacques Cartier River fault, which can act as both a barrier and a preferential pathway, provided permeability contrasts with the surrounding rock are at least two orders of magnitude.